2020
DOI: 10.2478/acph-2021-0015
|View full text |Cite
|
Sign up to set email alerts
|

Piperine: Chemical, biological and nanotechnological applications

Abstract: Piperine (PIP) is an alkaloid present in several species of piper, mainly Piper nigrum Linn. and P. longum, among other species. The present article provides a comprehensive review of PIP research in the last years concerning its chemical properties, synthesis, absorption, metabolism, bioavailability and toxicity. The reviewed PIP literature has shown many pharmacological properties, such as antidiabetic, antidiarrheal, antioxidant, antibacterial, and anti-parasitic activity of PIP. However, its low solubility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 123 publications
0
28
0
Order By: Relevance
“…PIP has many pharmacological properties, such as antidiabetic, antidiarrheal, antioxidant, antibacterial, and antiparasitic activity [5]. It also reduces cholesterol uptake and enhances translocation of cholesterol transporter proteins, as reported by Christian Rafael Quizia et al [5]. PIP-loaded NPs showed a more significant inhibitory effect on seizure-related behavioral signs compared to the free PIP [6].…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…PIP has many pharmacological properties, such as antidiabetic, antidiarrheal, antioxidant, antibacterial, and antiparasitic activity [5]. It also reduces cholesterol uptake and enhances translocation of cholesterol transporter proteins, as reported by Christian Rafael Quizia et al [5]. PIP-loaded NPs showed a more significant inhibitory effect on seizure-related behavioral signs compared to the free PIP [6].…”
Section: Introductionmentioning
confidence: 92%
“…and P. longum. PIP has many pharmacological properties, such as antidiabetic, antidiarrheal, antioxidant, antibacterial, and antiparasitic activity [5]. It also reduces cholesterol uptake and enhances translocation of cholesterol transporter proteins, as reported by Christian Rafael Quizia et al [5].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Other traditional medicine systems, such as TCM, use black pepper to treat various pains (e. g. muscle aches and headaches), rheumatism, and infections such as strep throat and influenza, as well as to improve blood circulation [3]. Based on its utilisation in traditional medicine, extensive in vitro and in vivo studies regarding the bioactivity of piperine have been conducted and reported: a very wide range of bioactivity, including anti-inflammatory, antimicrobial, anticancer, anti-diabetic, anti-obesity, antihyperlipidemia, anticonvulsant, antidepressant, antiepileptic, neuroprotective, and hepatoprotective [1,2,4,5]. Recent studies on piperine by in silico method showed that piperine has antiviral activity against the SARS-CoV-2 virus that caused COVID-19, through inhibition of virus replication and the ACE-2 receptor [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…fasciculata (Solanaceae) have promising activity against Leishmania amazonensis [ 11 ]; (ii) extracts from leaves and stem bark of Crescentia cujete (Binoniacea) have anti-inflammatory and antibacterial in vitro activities; possibly related to tannins, flavonoids, flavones and flavonols [ 12 ]; (iii) extracts from Clusia (Clusiaceae) species and Malpighia glabra (Malpighiaceae) rich in carotenoids and flavonoids present potent antioxidant activity [ 13 , 14 , 15 ]; and (iv) aqueous extract pf Rheedia longifolia (Clusiaceae) leaves has analgesic and anti-inflammatory in vivo activities and low toxicity [ 16 ]. Additionally, natural products from Piper species (Piperaceae) display broad biological roles [ 17 , 18 , 19 , 20 , 21 ], including antiprotozoal effects [ 22 ]. Additionally, a chalcone isolated from inflorescences of P. aduncum [ 23 ] and an essential oil and the ethanolic extract from leaves of P. marginatum [ 24 ] also present promising in vitro effect against L. amazonensis .…”
Section: Introductionmentioning
confidence: 99%